Response of Growth and Seed Yield of Mung Bean (Vigna radiata L.) to Chicken Manure and Banana Hump Liquid Organic Fertilizer Application - Kurniasari, Leli; Anggriawan, Feri; Lestari, Sri Ayu Dwi; Sulistyo, Nanti Bambang Eko; Syahban, Rahmat Ali; Rahayu, Sri (The University of Lampung, 2024)
Mung bean is highly important legume crop in Indonesia. Attempts to improve the yield and quality of mung bean seeds can be done through improving the planting media by adding organic fertilizer. The objective of this study was to determine the response of growth and seeds production of mung bean due to chicken manure and banana hump organic fertilizer. The research was performed in the greenhouse at the Balai Pengujian Standar Instrumen Tanaman Aneka Kacang (BSIPTAKA), Muneng Probolinggo. This study was structured in a factorial block design with three replications executed randomly. The first factor was doses of CM consisting of 0, 8.3, 16.7, and 25 ton/ha. The second factor was concentrations of banana hump liquid organic fertilizer (LOF) consisting of 0, 10, 20, and 30 ml/L. The result showed that doses of CM had a significant effect on plant height at 10 DAP, seed weight per plant, and seed yield. The interaction between CM doses and banana hump LOF was able to increase leaf chlorophyll index at 30 DAP. Combination of 16.7 ton/ha CM and 20 ml/L banana hump LOF produced the highest average chlorophyll index of 55.07 CCI. Keywords: Chlorophyll index, Manure, Mung bean, Organic fertilizer, Seed.